Controls and Constraints - Taylor, Steven (Organizational Aesthetics, 2015)
We teach managers to seek control and eliminate constraints. In contrast artists often create constraints and lose control. That may be something of an exaggeration, but it also has a ring of truth. As a manager I saw constraints as something generally negative and control as something generally positive - lack of control was a sin when pointed out by auditors. In contrast as an artist I often intentionally construct complex constraints for my work and scoff at control, saying something like, "control is an illusion". As a scholar I wonder about the implications of this difference.